2015
DOI: 10.1002/jnr.23625
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for early and progressive ultrasonic vocalization and oromotor deficits in a PINK1 gene knockout rat model of Parkinson's disease

Abstract: Parkinson disease (PD) is a progressive neurodegenerative disease that leads to a wide range of motor and non-motor deficits. Specifically, voice and swallow deficits manifest early, are devastating to quality of life, and are difficult to treat with standard medical therapies. The pathological hallmarks of PD include accumulation of the presynaptic protein alpha-synuclein as well as degeneration of substantia nigra dopaminergic neurons. However, there is no clear understanding of how or when this pathology co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
188
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 95 publications
(218 citation statements)
references
References 59 publications
26
188
3
Order By: Relevance
“…Changes in vocalizations in animal models of PD have been demonstrated in several model species. Common findings in rodents with parkinsonism induced by neurotoxin or transgenesis are reduced number of calls, reduced intensity of calls, and reduced call-complexity [24, 41, 42], most of which are improved with behavioral therapy (vocal exercise) [25, 43] but not with levodopa [44]. Studies in common marmosets with neurotoxin-induced parkinsonism have only reported a reduced number of vocalizations, without performing any further acoustic analyses [45, 46, 47, 48, 49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in vocalizations in animal models of PD have been demonstrated in several model species. Common findings in rodents with parkinsonism induced by neurotoxin or transgenesis are reduced number of calls, reduced intensity of calls, and reduced call-complexity [24, 41, 42], most of which are improved with behavioral therapy (vocal exercise) [25, 43] but not with levodopa [44]. Studies in common marmosets with neurotoxin-induced parkinsonism have only reported a reduced number of vocalizations, without performing any further acoustic analyses [45, 46, 47, 48, 49].…”
Section: Discussionmentioning
confidence: 99%
“…These voice and speech deficits are mostly refractory to standard of care medical treatment (levodopa) [20] or surgical treatment (deep brain stimulation) [21, 22]. Although voice and speech changes are not commonly reported by patients with PD until the later stages of the disease [23], there is recent evidence of preclinical communication changes, both in humans [3] and in animal models [24, 25]. Study of vocal changes early in neurodegenerative diseases can result in greater understanding of disease pathology, progression, and identification of behavioral biomarkers, that could improve diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasonic Vocalizations (USVs) are a useful tool for inferring affective states in the rat and have been incorporated in research paradigms modeling important human conditions such as drug abuse, [1][2][3] depression, fear, and anxiety disorders, 4 Parkinson disease, 5 and aging. 6 Moreover, USVs are a useful tool for examining the neurobiological substrates of reward.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in models of Parkinson disease and neurodegeneration, it has been shown that dopamine depleting lesions and aging produce changes in the acoustic features of USVs, such as decreases in amplitude and reductions in fundamental frequency bandwidth. 5,[10][11][12] Notably, these changes affect the acoustic qualities of vocalizations rather than the quantity of observed USVs. Moreover, it has been convincingly shown that repeated training of USVs improves the vocal deficits induced by dopamine depleting lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Several pharmacological (dopamine receptor antagonists), neurotoxin (6-hydroxydopamine) and genetic rodent models (overexpression of human wild-type alpha synuclein under the Thy-1 promotor in the mouse and with AAV2/5 in the rat) of PD demonstrate degradation in acoustic features of USVs (Ciucci et al, 2009; Ciucci et al, 2007; Gombash et al, 2013; Grant et al, 2014; Ringel, Basken, Grant, & Ciucci, 2013; Wright, Dobosiewicz, & Clarke, 2013). Specifically, recent evidence from our laboratory indicates that in rats, the complete knockout (KO) of PTEN-induced putative kinase 1 ( PINK1 ), a gene associated with autosomal recessive, early onset PD in human populations (Bonifati et al, 2005; Kawajiri, Saiki, Sato, & Hattori, 2011; Tan et al, 2006; Valente et al, 2004), results in early and progressive reductions of USV bandwidth, peak frequency, and intensity as compared to wild-type (WT) controls (Grant, Pultorak, Kelm-Nelson, & Ciucci, 2013). The impact of these PINK1 KO deficits in USV production on social communication is unknown.…”
Section: Introductionmentioning
confidence: 99%